Using Statistical Deformable Models to Reconstruct Vocal Tract Shape from Magnetic Resonance Images - Vasconcelos, Maria João (2021)
The mechanisms involved in speech production are complex and have thus been subject to growing attention by the scientific community. It has been demonstrated that magnetic resonance imaging (MRI) is a powerful means in the understanding of the morphology of the vocal tract